International business and regulatory compliance: an Australian experience. (18th January 2006) - Carroll, Peter; McGregor-Lowndes, Myles
The issue addressed in this paper is the growing challenge that the management of regulatory compliance poses for firms. The OECD has argued that we are seeing the development of what can be called the 'New Regulatory State' (OECD 1997). In that context it identifies a number of increasing trends, including the need for effective regulatory reform as governments pursue a less directly interventionist role in business. In addition, it notes the need for new systems of governance, national and global, that emphasise industry and firm self-regulation, rather than intrusive, traditional, 'command and control', regulation by government. Both of these trends have important implications for business.